THE GEOGRAPHICAL BOUNDARIES OF AELIA (JERUSALEM) DURING THE BYZANTINE RULE (135 -638 A.D): ISLAMIC PERSPECTIVE - Al-Tel, Othman Ismail (Journal of Al-Tamaddun, 2012)
The aim of this paper is to attempt to establish the topography and geographical boundaries of the Jerusalem. This spans the time when clear boundaries were set for this region by the Byzantine Emperor Hadrian in 135 A.D when he named it Aelia, until the arrival of ?Umar Ibn al-KhattÄb in it on the eve of the first Islamic conquest of the Jerusalem. This study will be useful if we attempt to find some explanations for the reasons behind the contradictions in the Islamic sources regarding many issues related to the first Islamic conquest.